Community-Level Characteristics of Timely PCP Follow-Up Care and Post-Discharge ER Usage. Issue 1 (2nd January 2023) - Mitchell, Jordan; Li, Xiao; Decker, Phillip J.
Abstract: Achieving equitable access has been a central goal in healthcare for years; access by low-income Americans is a major concern for policymakers. We examined the differences in post-discharge primary care follow-up visits and 30-day post discharge ER visits across several characteristics. The results suggest that higher housing density, percent minority population, percent unemployed, and percent uninsured point to lower rates of PCP follow-up care and higher rates of post-discharge ER visits. These findings have implications for developing cost-effective programs targeting hospital to PCP communication, especially in densely populated areas.